PEMBUATAN PRODUK JASA KONSULTASI DESIGN INTERFACE REKAM MEDIS BERBASIS WEB HOSTING DENGAN MENGGUNAKAN DREAMWEAVER MX.8 DI ID HOSTINGER - Yudho Trisnanto, Puguh (DINAMIKA DOTCOM, 2017)
Product consulting medical records by using DWMX.8 on WEB ID Hostinger a web application software that is required by many companies / hospitals and health centers to improve and simplify the performance of employees to be more effective. The computer network consists of LAN, WAN and MAN. LAN (Local Area Network) is a network that is internal and usually privately owned in the medium and small companies tau are usually sized to several kilometers. (Sopandi, 2010: 2) Product consulting medical records by using DWMX.8 on WEB ID Hostinger using web domain ID Hostinger. With the WEB ID Hostinger possible to make products services consulting medical records must also be different user rights and the cost of the care network can immediately known. Use of WEB ID Hostinger to obtain database services are easily controlled and can be used regularly and efficiently without spending requires a lot of capital to create products consulting medical records.Â Keywords: Hostinger ID, Domain, Consulting Services, Computer Networking, Medical Record